Apnea–hypopnea index decreased significantly after nasal surgery for obstructive sleep apnea: A meta-analysis. Issue 5 (February 2017) - Wu, Jun; Zhao, Guoqiang; Li, Yunchuan; Zang, Hongrui; Wang, Tong; Wang, Dongbo; Han, Demin
Abstract: Background: Nasal surgeries have been applied to obstructive sleep apnea (OSA) patients with nasal obstruction for decades. However, the efficiency of nasal surgery in improving OSA remains controversial. The aim of this study was to identify whether isolated nasal surgery can improve apnea–hypopnea index (AHI). Methods: Computerized searches were performed in MEDLINE, Web of Science, Cochrane Library, and Scopus from January 1, 2000 to April 30, 2016. A total of 18 articles and 587 participants were included. There were 1 randomized controlled trials, 2 nonrandomized trials, 11 prospective studies, and 4 retrospective studies. Data regarding study design (prospective/retrospective clinical trial, randomized, and controlled), population size, participant characteristics (age, gender, and body mass index), surgical intervention, and outcomes (AHI, Epworth sleep scale [ESS]) was collected. Results: Statistically significant improvement in AHI (subgroup 1: weighted mean difference [WMD] [95%confidence interval (CI)], −4.17 [−7.62, −0.73]; subgroup 2: WMD [95%CI], −4.19 [−7.51, −0.88]; overall: WMD [95%CI], −4.15 [−6.48, −1.82]) and ESS (subgroup 1: WMD [95%CI], −2.14 [−3.08, −1.19]; subgroup 2: WMD [95%CI], −4.70 [−5.95, −3.44]; overall: WMD [95%CI], −4.08 [−5.27, −2.88]) was revealed. Conclusion: Both AHI and ESS improved significantly after isolated nasal surgery, but the improvement of AHI is slightly significant. Future randomized controlled trials are needed to confirm the long-term benefits of nasal surgery on OSA.